2021
DOI: 10.1007/s12040-021-01737-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in carbon and nitrogen stable isotopes of Strobilanthes kunthianus leaf: Its photosynthetic efficacy and water-use efficiency in a warming climate

Abstract: Carbon assimilation in plants depends on both atmospheric CO 2 uptake and internal (non-atmospheric) CO 2 . To understand this mechanism in Strobilanthes kunthianus (an endemic pleitesial plant), we studied the leaf epidermal morphology, stomatal index (SI), cystoliths, carbon and nitrogen isotopes (d 13 C leaf , d 15 N leaf ) in herbarium samples collected during the bloom in 1958, 1970 and 2018 from Munnar region, India. The leaf epidermal morphology is xerophytic characterized by long, twisted and branched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The δ 13 C of flower and pollen also correlates with difference of ≤ 1.0 to 2.0‰ with the leaf samples of parent plant (Farooqui et al, 2021). Therefore, δ 13 C of bulk pollen (more likely to be preserved rather than leaf/stem in the sediments) could provide clue to pollen assemblages in the sedimentary archives where species response can vary the values significantly representing past climatic conditions and its equilibrium with the vegetation (Fardusi et al, 2016;Farooqui et al, 2021). There is a growing interest in understanding the morphology and geochemistry of pollen for climate-vegetation changes and environmental informations supported by species-level identification (Pappas et al, 2003;Julier et al, 2016;Zimmermann et al, 2016).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The δ 13 C of flower and pollen also correlates with difference of ≤ 1.0 to 2.0‰ with the leaf samples of parent plant (Farooqui et al, 2021). Therefore, δ 13 C of bulk pollen (more likely to be preserved rather than leaf/stem in the sediments) could provide clue to pollen assemblages in the sedimentary archives where species response can vary the values significantly representing past climatic conditions and its equilibrium with the vegetation (Fardusi et al, 2016;Farooqui et al, 2021). There is a growing interest in understanding the morphology and geochemistry of pollen for climate-vegetation changes and environmental informations supported by species-level identification (Pappas et al, 2003;Julier et al, 2016;Zimmermann et al, 2016).…”
mentioning
confidence: 78%
“…About 175 different species were analysed for δ 13 C in pollen, leaf and stem tissue and it was found that δ 13 C of pollen correlated strongly with the parent leaf material (Jahren, 2004). The δ 13 C of flower and pollen also correlates with difference of ≤ 1.0 to 2.0‰ with the leaf samples of parent plant (Farooqui et al, 2021). Therefore, δ 13 C of bulk pollen (more likely to be preserved rather than leaf/stem in the sediments) could provide clue to pollen assemblages in the sedimentary archives where species response can vary the values significantly representing past climatic conditions and its equilibrium with the vegetation (Fardusi et al, 2016;Farooqui et al, 2021).…”
mentioning
confidence: 99%